Homoeopathic remedies:the physics of healing with microdoses - Upasi, Venkata Subbareddi (Запорізький державний медичний університет, 2015)
Hippocrates wrote of curing 'like with like' more than 2,000 years ago but it was formally systematized by the German physician Samuel Hahnemann (1755–1843) in 1796. This implies that substances that cause disorder in healthy people are used as medicines to treat similar symptoms experienced by sick patients. The properties of the chosen medicine should be as similar as possible to the symptoms and signs of the disease, the patient’s physical build, personality, temperament and genetic predispositions.